2017
DOI: 10.1186/s12947-017-0116-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of strain parameters in dyssynchronous heart failure between speckle tracking echocardiography vendor systems

Abstract: BackgroundAlthough mechanical dyssynchrony parameters derived by speckle tracking echocardiography (STE) may predict response to cardiac resynchronization therapy (CRT), comparability of parameters derived with different STE vendors is unknown.MethodsIn the MARC study, echocardiographic images of heart failure patients obtained before CRT implantation were prospectively analysed with vendor specific STE software (GE EchoPac and Philips QLAB) and vendor-independent software (TomTec 2DCPA). Response was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Overall, we found very wide variation in measures between all the software packages and settings for longitudinal and circumferential TTPSD. Although TTPSD may be reproducible amongst the same vendors in adults [4,22] and children [3], our data suggest avoidance of interchanging the TTPSD measures between studies using different vendor software packages and settings [3].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Overall, we found very wide variation in measures between all the software packages and settings for longitudinal and circumferential TTPSD. Although TTPSD may be reproducible amongst the same vendors in adults [4,22] and children [3], our data suggest avoidance of interchanging the TTPSD measures between studies using different vendor software packages and settings [3].…”
Section: Discussionmentioning
confidence: 77%
“…Since ventricular synchrony measures are associated with life-threatening arrhythmias, heart failure, and mortality in pediatric populations [7,8], understanding the variability between vendors might allow the generalizability of these findings across echocardiography laboratories. Van Everdingen et al demonstrated minimal differences in longitudinal TTPSD with adults (patients had a range of structurally normal hearts and varying degrees of cardiac function and arrhythmias) between QLAB (10.0) and TomTec (1.2.1.2) [4]. Values were lower (more synchronous) in QLAB compared to the TomTec.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is significant variation in technology between echocardiography system vendors. 30 In addition, our current study was performed using the Philips IE33 platform in which segmental strain reproducibility is considered suboptimal.…”
Section: Limitationsmentioning
confidence: 99%